RNA decoys: An emerging component of plant regulatory networks? - Banks, Isaac R. (Landes Bioscience, 2012)
The role of non-coding RNAs (ncRNAs), both short and long ncRNAs, in the regulation of gene expression has become evident in recent years. Non-coding RNA-based regulation is achieved through a variety of mechanisms; some are relatively well-characterized, while others are much less understood. MicroRNAs (miRNAs), a class of endogenous small RNAs, function as master regulators of gene expression in eukaryotic organisms. A notable, recently discovered role for long ncRNAs is that of miRNA decoys, also referred to as target mimics or sponges, in which long ncRNAs carry a short stretch of sequence sharing homology to miRNA-binding sites in endogenous targets. As a consequence, miRNA decoys are able to sequester and inactivate miRNA function. Engineered miRNA decoys are also efficacious and useful tools for studying gene function. We recently demonstrated that the potential of miRNA decoys to inactivate miRNAs in the model plants Arabidopsis thaliana and Nicotiana benthamiana is dependent on the level of sequence complementarity to miRNAs of interest. The flexibility of the miRNA decoy approach in sequence-dependent miRNA inactivation, backbone choice, ability to simultaneously inactivate multiple miRNAs, and more importantly, to achieve a desirable level of miRNA inactivation, makes it a potentially useful tool for crop improvement. This research addendum reports the functional extension of miRNA decoys from model plants to crops. Furthermore, endogenous miRNA decoys, first described in plants, have been proposed to play a significant role in regulating the transcriptome in eukaryotes. Using computational analysis, we have identified numerous endogenous sequences with potential miRNA decoy activity for conserved miRNAs in several plant species. Our data suggest that endogenous miRNA decoys can be widespread in plants and may be a component of the global gene expression regulatory network in plants.